The progress in titanium alloys used as biomedical implants: From the view of reactive oxygen species - Yang, Jun; Liu, Chang; Sun, Hui; Liu, Ying; Liu, Zhaogang; Zhang, Dan; Zhao, Gang; Wang, Qiang; Yang, Donghong (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium and Titanium alloys are widely used as biomedical implants in oral and maxillofacial surgery, due to superior mechanical properties and biocompatibility. In specific clinical populations such as the elderly, diabetics and patients with metabolic diseases, the failure rate of medical metal implants is increased significantly, putting them at increased risk of revision surgery. Many studies show that the content of reactive oxygen species (ROS) in the microenvironment of bone tissue surrounding implant materials is increased in patients undergoing revision surgery. In addition, the size and shape of materials, the morphology, wettability, mechanical properties, and other properties play significant roles in the production of ROS. The accumulated ROS break the original balance of oxidation and anti-oxidation, resulting in host oxidative stress. It may accelerate implant degradation mainly by activating inflammatory cells. Peri-implantitis usually leads to a loss of bone mass around the implant, which tends to affect the long-term stability and longevity of implant. Therefore, a great deal of research is urgently needed to focus on developing antibacterial technologies. The addition of active elements to biomedical titanium and titanium alloys greatly reduce the risk of postoperative infection in patients. Besides, innovative technologies are developing new biomaterials surfaces conferring anti-infective properties that rely on the production of ROS. It can be considered that ROS may act as a messenger substance for the communication between the host and the implanted material, which run through the entire wound repair process and play a role that cannot be ignored. It is necessary to understand the interaction between oxidative stress and materials, the effects of oxidative stress products on osseointegration and implant life as well as ROS-induced bactericidal activity. This helps to facilitate the development of a new generation of well-biocompatible implant materials with ROS responsiveness, and ultimately prolong the lifespan of implants.